Tingkat Pemahaman Mahasiswa Preklinik dan Klinik Fakultas Kedokteran dan Kesehatan Universitas Muhammadiyah Jakarta terhadap Kaidah Dasar Bioetika dan Perilaku Penilaian Moral - Muchlis, Ahmad; Syafruddin, Amir; Tubarad, Gladys Dwiani Tinovella; Sabrina, Annaya Noor (HB PRESS, 2024)
Essentially, a doctor is evaluated not only by his capability to treat disease, but also by his ability to make choices in order to keep both the patient and the doctor in question while adhering to the applicable norms and regulations. As a result, medical students must understand the fundamental principles of bioethics and make proper ethical judgements. The objective of this research is to evaluate preclinical and clinical students' awareness of basic bioethics concepts at Muhammadiyah University Jakarta's Faculty of Medicine and Health. The Simple Cross-sectional approach was used on 83 students, 43 preclinical and 40 clinical, by using study instruments Basic Bioethical Rules Test (KDB) and Moral Research Test (UPM). The study's end goal is to uncover preclinical and clinical students' thoughts on how KDB and UPM might be implemented, not just as information that can be formed as output in the form of writing and scientific infographic posters.